2019
DOI: 10.1002/nop2.428
|View full text |Cite
|
Sign up to set email alerts
|

Nursing research priorities based on CINAHL database: A scoping review

Abstract: Aim To analyse nursing research based on the CINAHL database to identify research priorities for nursing. Design A scoping literature review was conducted. The CINAHL Plus (EBSCO) Full Text was searched between 2012–2018. Methods Out of 1522 original publications, 91 fulfilled the inclusion criteria. The Joanna Briggs Institute critical appraisal tools were applied. Data were analysed by a thematic analysis method. Results A strong emphasis should be put on development and evaluation of nursing theories and, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 100 publications
(195 reference statements)
0
26
0
4
Order By: Relevance
“…Our study confirmed, as in the Swedish context, that an element in favor of nursing research has been the development of doctoral education programs within nursing science, which was made possible by the increase in the number of registered nurses that have the PhD degree. Certainly, nursing research has increased in both quantity and complexity, according to a recent scoping review that identified four global research priorities: nursing theory development, methodology of nursing research, expertise in advanced nursing and professional nursing practice [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study confirmed, as in the Swedish context, that an element in favor of nursing research has been the development of doctoral education programs within nursing science, which was made possible by the increase in the number of registered nurses that have the PhD degree. Certainly, nursing research has increased in both quantity and complexity, according to a recent scoping review that identified four global research priorities: nursing theory development, methodology of nursing research, expertise in advanced nursing and professional nursing practice [17].…”
Section: Discussionmentioning
confidence: 99%
“…While, in a study involving seven countries, it was noted as a concern that research in nursing science may be compromised due to the primary supervision of nursing doctoral students by non-nurse supervisors [10], in our context it does not appear as a threat with a sufficient degree of consensus, although this phenomenon does exist. Nevertheless, it has been recently pointed out that nursing as a discipline is rather young and the theoretical development of nursing knowledge is even more recent [17]. The main difficulty in this field is the lack of connection between the healthcare institutions and the university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O desenvolvimento de competências e habilidades está entre as principais prioridades de pesquisa de Enfermagem, uma vez que estudos mais robustos são necessários para o avanço do conhecimento de Enfermagem em diversas áreas da prática 18 . Especificamente, habilidades relacionadas à metodologia de pesquisa em Enfermagem e expertise em prática avançada de Enfermagem foram identificadas como principais prioridades de Enfermagem, as quais o programa de treinamento já aborda.…”
Section: Conclusão E Implicações Para a Práticaunclassified
“…With the dramatically increasing amount of the published papers in health care, the expectations from nurse scientists for acquiring knowledge and skills for verifying the quality of research have been doubled (Erickson & Pappas, 2020). Consequently, verifying the findings of research has become one of the essential skills for preventing poor research designs, HARKing (Hypothesizing After the Results are Known), p-hacking, and selective reporting of positive findings (Hopia & Heikkilä, 2020;Miyakawa, 2020). Without this fundamental effort, the pipelines of nursing research, scientific evidence, and nursing practice may not be firmly connected (Figure 1).…”
mentioning
confidence: 99%